2012
DOI: 10.1061/(asce)cc.1943-5614.0000266
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Behavior of CFRP Precast Prestressed Decked Bulb T -Beams

Abstract: This study introduces an innovative scheme of bridge superstructure for expedited construction, improved serviceability, and extended life span. The new bridge superstructure is assembled from precast prestressed decked bulb T-beams reinforced and prestressed with corrosion-free fiber-reinforced polymer (FRP) materials. An experimental investigation accompanied by analytical and numerical simulations was developed to evaluate the performance of the newly developed beams. Through the experimental investigation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…It was also concluded that the effect of prestress at transfer and concrete strength should be considered while estimating transfer length. Grace et al [12] conducted an experimental and analytical research to study flexural behaviour of decked bulb T-beams reinforced and prestressed with different kinds of FRP materials. Test results showed that the performance of CFRP tendons or CFCC strands reinforced beams was comparable to that of the control beam, prestressed and reinforced with conventional steel strands and bars, at both service and ultimate limit states.…”
Section: State Of the Fieldmentioning
confidence: 99%
“…It was also concluded that the effect of prestress at transfer and concrete strength should be considered while estimating transfer length. Grace et al [12] conducted an experimental and analytical research to study flexural behaviour of decked bulb T-beams reinforced and prestressed with different kinds of FRP materials. Test results showed that the performance of CFRP tendons or CFCC strands reinforced beams was comparable to that of the control beam, prestressed and reinforced with conventional steel strands and bars, at both service and ultimate limit states.…”
Section: State Of the Fieldmentioning
confidence: 99%
“…For example, Beam C100-S6-4 is a beam prestressed longitudinally with CFCC strands to a level of 100 kip, provided with steel stirrups at spacing of 6 in., and loaded at a distance equal to 4d from the support, where d is the effective depth of the beam. Detailed prestressing, construction, and curing techniques of the beams can be found in Grace et al (2012a) and Rout (2013). The concrete compressive strength averaged 44 MPa (6.4 ksi) at the time of prestress transfer and 62 MPa (9 ksi) after 28 days.…”
Section: Phase Ii: Prestressed Decked Bulb T-beams With Cfcc/steel Stmentioning
confidence: 99%
“…Although there is a higher initial cost of construction using FRP materials as a primary reinforcement, life-cycle cost analysis has proven that the overall cost, including maintenance and replacement costs, are much lower (Eamon et al 2012;Grace et al 2012b). Numerous studies have addressed structures internally reinforced or prestressed with longitudinal CFRP reinforcement (Grace et al 2012a(Grace et al , 2013a. However, the use of CFRP materials as shear reinforcement in the form of stirrups has not been thoroughly evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e CFRP-CFST pile of high-pile wharfs has three corrosion zones: the atmospheric zone, the dry and wet alternating zone, and the underwater zone. Oxygen and water are indispensable for the occurrence and development of corrosion [4][5][6][7]. e underwater zone lacks enough oxygen, and the water supply in the atmospheric zone is insufficient.…”
Section: Introductionmentioning
confidence: 99%